Performance and Effectiveness of Catholic Schools in Tagum - Anduyan, Dennis B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
Schools and education authorities became increasingly aware of the need to be effective due to the pressures for accountability brought by national and local government levels and school stakeholders in relation to the demands of the new educational system. This study determined the performance of the schools and effectiveness of the administrators with the human resource development in the selected Catholic schools in Tagum, Davao del Norte. Findings of the study served as inputs for the improved administrative manual and school improvement plan. The study utilized mixed methods among the 250 participants. The instrument focused on the indicators based on the Fund for Assistance to Private Education. Vision and mission, curriculum and instruction, faculty development, student development, physical plant and facilities, financial and business administration, and school and community involvement were considered advanced and were sustained for a longer period of time. The administrators’ level of implementation in the human resource management and development functions was considered adequate. The implementation in terms of benefits, remuneration and evaluation were also evident. Employment policy, work regulations, discipline, leave of absence, and grievance and complaints were substantially observed. There is a significant relationship between the performance of schools and administrators’ effective implementation of human resource management and development functions. There was shared understanding on roles, responsibilities, and expectations by the stakeholders.